Effect of Variable Conditions of Exposure on the Physical and Mechanical Properties of Blockboards - Zeleniuc, Octavia; Coșereanu, Camelia (MDPI AG, 2022)
The growing demand for wood and the continued increase of the raw material price have resulted in companies using more efficient wood resources in wood-based products such as blockboard. These boards are used in the field of interior design, especially. The aim of this research was to evaluate the effect of variable environmental conditions on the physical and mechanical properties of blockboard (BK). Two types of commercial BK were exposed in variable environmental conditions (kitchen, bathroom and climatic chamber) for three months. The BK structures were composed of veneer (V) and high-density fibreboards (HDF) for the face sheets and glued, solid wood, resinous strips for the core. The temperature and relative humidity of the air (RH) ranged from 18 °C to 25 °C and from 25% to 90%, respectively. In the climatic chamber (CC), the dynamics of the parameter variations were different than in the other two exposure climates, being determined by the programmed cyclic changes in RH. The changes observed on physical and mechanical properties were more extreme for the blockboards tested in the CC than in the kitchen (K) and bathroom (Ba). After 3 months of exposure in the CC, the thickness and weight of the boards increased by 1.8 and 1.1 times, respectively, for veneered BK, and by 4.4 and 0.4 times, for BK with HDF faces, compared to values recorded in the kitchen. The panels exposed in the CC exhibited the highest increase in moisture content (MC): 41% for veneered BK and 82% for BK with HDF faces after three months of exposure, followed by those exposed in the bathroom and kitchen. Increases in MC determined decreases of flexural properties and soundness surfaces, more evident for HDF face structures compared to V ones.
Keywords: blockboard; environmental conditions; moisture content; physical-mechanical properties; dimensional stability; warpage